2017
DOI: 10.1111/jsr.12530
|View full text |Cite
|
Sign up to set email alerts
|

A Sleep Position Trainer for positional sleep apnea: a randomized, controlled trial

Abstract: We tested the effect of the Sleep Position Trainer, a vibrational device, for positional sleep apnea in an open, randomized controlled trial with 101 patients, where 52 patients were allocated to Sleep Position Trainer and 49 patients to a non-treatment control group for 2 months (Part 1). All patients were then followed as a cohort for a period of 6 months with use of the Sleep Position Trainer (Part 2). The participants were assessed with polygraphy at entry, and after 2 and 6 months. The mean apnea-hypopnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…Nevertheless, these nine subjects provided relevant information to determine how the positional treatment worked on them. As there is evidence of the efficacy of vibrational devices in preventing certain sleep positions [ 46 , 47 , 48 ], the results obtained can be reliably interpretated as a proof-of-concept confirming the feasibility of the app to conduct positional therapy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Nevertheless, these nine subjects provided relevant information to determine how the positional treatment worked on them. As there is evidence of the efficacy of vibrational devices in preventing certain sleep positions [ 46 , 47 , 48 ], the results obtained can be reliably interpretated as a proof-of-concept confirming the feasibility of the app to conduct positional therapy.…”
Section: Discussionmentioning
confidence: 61%
“…The summarized table information is the method currently used in most clinical departments to assess sleep position. Usually when positional treatment, such as the TBT technique [ 44 , 45 ] or other vibrational devices [ 46 , 47 , 48 ] are applied to a patient, the efficacy of this technique is validated upon the summarized information on how much time has been spent in a certain sleep position. However, recent studies have demonstrated how a higher resolution sleep position would be needed to better diagnose and monitor the positional occurrence of diseases, such as OSA [ 37 , 38 ], for which we believe that the combination of information provided by the ‘SleepPos’ app allows a better assessment of the sleep position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, smartphones could have the potential to precisely monitor sleep position while, at the same time, providing diagnosis for OSA [ 38 , 41 , 52 ]. Furthermore, they could even incorporate the ability to verify or apply positional therapy for several days, similar to what other devices already do [ 60 , 61 ]. Monitoring a patient’s sleep position for multiple days would allow the effect of any treatment to be assessed, and modified if necessary, in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Laub et al . () conducted a randomized controlled trial with 101 apnea patients where more than half of them were allocated to the Sleep Position Trainer and the remainder to a non‐treatment control group for 2 months. Patients were followed‐up and the main outcome was that the Sleep Position Trainer decreased supine sleep time significantly from 47 to 17% in the active treatment group, whereas in the control group the corresponding values were 48–39%.…”
Section: Sleep and Breathing Disordersmentioning
confidence: 99%